Pentecostals, Politics, and Religious Equality in Argentina. - Aasmundsen, Hans Geir. (Boston : BRILL, 2016)
Pentecostalism in Argentina provides an account of the socio-political aspects of the fastest growing religion of our time, Pentecostalism, in an Argentina that has moved from an unstable dictatorship to a modern democracy in the time of globalization.
Intro -- Pentecostals, Politics, and Religious Equality in Argentina -- Copyright -- Contents -- Preface -- Abbreviations -- Introduction -- 1 Historical Background -- 2 Theoretical Framework -- 3 From Negative to Positive Dualism -- 4 The Struggle for Religious Freedom and Equality -- 5 Pentecostalism and Politics -- 6 Conclusions and Final Remarks -- References -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books